The majority of a collection of U.S. Endocarditis enterococcus faecalis isolates obtained from 1974 to 2004 lack capsular genes and belong to diverse, non-hospital-associated lineages (2014)
Eighty-one endocarditis-derived Enterococcus faecalis isolates that were collected from individual patients in the United States between 1974 and 2004 were sequence typed and analyzed for the presence of various genes, including some previously associated with virulence. Overall, using our previously described trilocus sequence typing (TLST), 44 different sequence types (STs) were found within this collection; 26 isolates were singletons (a unique TLST sequence type [STT]), some STTs contained multiple isolates (up to 6 isolates), and 16% of the isolates (13 isolates) could be grouped by additional sequence typing into clonal cluster 21 (CC21). Of note, only four isolates (7%) of the 56 whose multilocus sequence types were determined were found to belong to one of the previously described hospital-associated clonal clusters CC2 and CC9, and only 15% and 37% of all isolates had high-level resistance to gentamicin and streptomycin, respectively, including 10% that were resistant to both. We also found that 64% of the isolates lacked the genes for production of capsule polysaccharide, which has been proposed to enhance the pathogenic potential of the hospital-associated clonal clusters. In summary, while our collection is not a random sample of cases of E. faecalis endocarditis, these results indicate that nonencapsulated strains belonging to non-hospital-associated lineages were predominant among endocarditis E. faecalis isolates recovered during this time period.